Genome-wide analysis of high risk human papillomavirus E2 proteins in human primary keratinocytes - Sunthamala, Nuchsupha (Genom Data, 2014)
The E2 protein is expressed in the early stage of human papillomavirus (HPV) infection that is associated with cervical lesions. This protein plays important roles in regulation of viral replication and transcription. To characterize the role of E2 protein in modulation of cellular gene expression in HPV infected cells, genome-wide expression profiling of human primary keratinocytes (HPK) harboring HPV16 E2 and HPV18 E2 was investigated using microarray. The Principle Components Analysis (PCA) revealed that the expression data of HPV16 E2 and HPV18 E2-transduced HPKs were rather closely clustered. The Venn diagram of modulated genes showed an overlap of 10 common genes in HPV16 E2 expressing HPK and HPV18 E2 expressing HPK. These genes were expressed with significant difference by comparison with control cells. In addition, the distinct sets of modulated genes were detected 14 and 34 genes in HPV16 E2 and HPV18 E2 expressing HPKs, respectively.